Poor drug adherence and lack of awareness of hypertension among hypertensive stroke patients in Kampala, Uganda: a cross sectional study. (December 2016) - Mugwano, Isaac; Kaddumukasa, Mark; Mugenyi, Levi; Kayima, James; Ddumba, Edward; Sajatovic, Martha; Sila, Cathy; DeGeorgia, Michael; Katabira, Elly
Abstract Background Raised blood pressure (BP) remains an important risk factor for cardiovascular diseases such as stroke. Adherence to therapeutic recommendations especially antihypertensive drugs is important in BP control. The aim of the study was to assess the stroke risk factors and levels of adherence among hypertensive patients with stroke in Kampala Uganda. Methods In a cross-sectional study we describe 112 hypertensive subjects with stroke from two Kampala city hospitals. A standardized pre-tested questionnaire was used to collect medical history, clinical details, radiological findings and laboratory data. Results A total of 112 hypertensive subjects with stroke were enrolled between May 2013 and April 2014. The median ages were 63.5 years (52.5–75.0) for the cases. Seventy percent (78/112) of the study participants had ischemic strokes. Only 17 % were adherent to anti-hypertensive medications. The main cause of non-adherence appears to be lack of knowledge. Conclusions Poor adherence of anti-hypertensive medications among hypertensive patients remains a big challenge in our setting. This has been attributed to lack of adequate knowledge and cost of the prescribed drugs. There is therefore an urgent need to promptly diagnose and educate hypertensive patients with emphasis on adherence to anti hypertensive drugs.